Tanggung Jawab Orang Tua dalam Mengajarkan Kasih terhadap Anak Menurut (Ulangan 6:5-7) - Apia Ahalapada; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
It should not be neglected because it is the parent's responsibility to meet the child's physical and spiritual needs. This article aims to examine in depth the responsibility of parents in instilling the value of love in their children based on the teachings of the Bible, especially Deuteronomy 6:5-7. Through a literature approach, this research will analyze the meaning of these verses and their implications in the context of child care in the modern era. that teaching love is not just about giving instructions, but also creating an environment full of love and attention. Through qualitative research, I explore or provide an understanding from a theological and practical perspective regarding the importance of their (parents') role or responsibility in forming children's character who has the character of Christ.